2020
DOI: 10.21037/atm-20-6629
|View full text |Cite
|
Sign up to set email alerts
|

Genomic analysis of the prognostic effect of tumor-associated neutrophil-related genes across 15 solid cancer types: an immune perspective

Abstract: Background: Tumor-associated neutrophils (TANs) have been a research hotspot in recent years.However, the role and relevant mechanisms of TANs in the tumor microenvironment (TME) have not yet been elucidated. Method: The ribonucleic acid (RNA) expression levels of fucosyltransferase 4 (FUT4) and elastase, neutrophil expressed (ELANE) in samples from The Cancer Genome Atlas (TCGA) (n=4,538) were analyzed. Receiver operating characteristic (ROC) curves were used to calculate the critical cutoff values, and diff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 22 publications
2
6
0
Order By: Relevance
“…Several proteins involved in carcinogenesis or leukemogenesis are increased for clinical responders (ANO6, CHI3L1, CTSG, ELANE and FGR), suggesting that the sensitivity to ATRA/VP additionally depends on more general functions involved in cancer development. This last hypothesis is further supported by previous observations describing associations between some of these network members and prognosis/survival in certain malignancies [ 80 , 81 , 82 , 83 ]. Finally, immune-mediated mechanisms may also be important for chemosensitivity because ATRA/VP reduces the levels of circulating T cells [ 5 ] and members of the neutrophil degranulation network are regarded as a possible leukemia-associated antigen (proteinase 3, PRTN3) and as a regulator of antileukemic immune reactivity (major histocompatibility complex, class I, B; HLA-B).…”
Section: Discussionsupporting
confidence: 83%
“…Several proteins involved in carcinogenesis or leukemogenesis are increased for clinical responders (ANO6, CHI3L1, CTSG, ELANE and FGR), suggesting that the sensitivity to ATRA/VP additionally depends on more general functions involved in cancer development. This last hypothesis is further supported by previous observations describing associations between some of these network members and prognosis/survival in certain malignancies [ 80 , 81 , 82 , 83 ]. Finally, immune-mediated mechanisms may also be important for chemosensitivity because ATRA/VP reduces the levels of circulating T cells [ 5 ] and members of the neutrophil degranulation network are regarded as a possible leukemia-associated antigen (proteinase 3, PRTN3) and as a regulator of antileukemic immune reactivity (major histocompatibility complex, class I, B; HLA-B).…”
Section: Discussionsupporting
confidence: 83%
“…MPO is a member of the heme peroxidase superfamily and is mainly expressed in neutrophils and monocytes. Studies have shown that MPO targeted therapy can show a good prognostic survival status in LUAD patients (35), which is consistent with the results of our survival analysis (P < 0.001). The results of molecular docking show that the compound Q of SAIN can speci cally bind to MPO protein (a nity = -8.8 kcal/mol).…”
Section: The Role Of Mpo and Nqo1 In Nsclc Patientssupporting
confidence: 92%
“…IL-6 polymorphism was associated with survival prognosis of non-small-cell lung cancer (nSCLC) [ 23 ]. A genomic analysis revealed that high ELANE expression in LUAD was associated with a good prognosis [ 24 ]. In esophageal squamous cell carcinoma, CASP4 served as a prognostic biomarker and is associated with poor prognosis [ 25 ].…”
Section: Discussionmentioning
confidence: 99%